Radiation-induced changes in the glycome of endothelial cells with functional consequences - Jaillet, Cyprien (Sci Rep, 2017)
As it is altered by ionizing radiation, the vascular network is considered as a prime target in limiting normal tissue damage and improving tumor control in radiation therapy. Irradiation activates endothelial cells which then participate in the recruitment of circulating cells, especially by overexpressing cell adhesion molecules, but also by other as yet unknown mechanisms. Since protein glycosylation is an important determinant of cell adhesion, we hypothesized that radiation could alter the glycosylation pattern of endothelial cells and thereby impact adhesion of circulating cells. Herein, we show that ionizing radiation increases high mannose-type N-glycans and decreases glycosaminoglycans. These changes stimulate interactions measured under flow conditions between irradiated endothelial cells and monocytes. Targeted transcriptomic approaches in vitro in endothelial cells and in vivo in a radiation enteropathy mouse model confirm that genes involved in N- and O-glycosylation are modulated by radiation, and in silico analyses give insight into the mechanism by which radiation modifies glycosylation. The endothelium glycome may therefore be considered as a key therapeutic target for modulating the chronic inflammatory response observed in healthy tissues or for participating in tumor control by radiation therapy.